Validity and reliability of the Malay questionnaire for olfactory disorders - Gima, Erica Anak (2023)
Background: Olfactory disorder is an umbrella term for a diverse group of smell problems. Numerous tests and questionnaires have been formulated to identify and test the severity of smell impairment, which is not readily available or not translated for the Malaysian population. We aimed to translate the Questionnaire for Olfactory Disorders (QOD), validate and test the reliability of the Malay questionnaire for olfactory disorders (mQOD). Methods: This was a cross sectional study conducted in two tertiary centres. A forward and back translation was done for the QOD. The translated questionnaire was distributed to subjects with self-reported smell disorders on day one and day seven. Internal consistency was analysed with Cronbach’s alpha and test retest reliability tested with intraclass correlation coefficient. Confirmatory factor analysis was done to test construct validity. Result: A total of 375 participants were recruited, 52 participants dropped out and 323 completed the questionnaire a second time. Cronbach’s alpha coefficient was 0.537 for P, 0.892 for LQ, 0.637 for S and 0.865 for VAS. The intraclass correlation coefficient (ICC) for domain scores were >0.9, while the ICC for all items were good to excellent. A three-factor model for mQOD showed acceptable fit with indices CMIN/DF=3.332, TLI=0.923, CFI=0.939, RMSEA=0.079 and SRMR=0.0574. Conclusion: The mQOD is a valid and reliable tool for assessing olfactory disorder in patients.